Pregnancy and peritoneal dialysis: an updated review - Thiam, Christopher Seong Lim; Fuah, Kar Wah (European Medical Journal, 2018)
Women who conceive while receiving peritoneal dialysis (PD) are at a high risk of encountering maternal and fetal complications. Although the occurrence of successful pregnancies in women with end-stage renal disease undergoing PD is becoming more common with advancing dialysis technology, women in this population must be monitored by a team of dedicated renal physicians and obstetric teams to ensure the best maternal and fetal outcomes are achieved. Given the haemodynamic advantages of PD over haemodialysis in pregnancy, PD therapy is the favoured renal replacement option in pregnant women with end-stage renal disease. This is particularly true when PD is initiated after conception or if pregnancy occurs within 1 year of starting PD. The management of anaemia, hypertension, dry weight adjustment, and dialysis regimen in a pregnant PD patient will undergo continuous adjustment to maintain haemodynamic and physiologic stability to meet the demands of the pregnancy-associated changes. In this article, the incidence and management of fetal and maternal complications and pregnancy outcomes in women receiving PD are reviewed based on the latest literature available.